Mit grecki w sztuce Etrusków na przykładzie olpe bucchero z motywem antropophagoi i legendą o argonautach: Greek Myth in Etruscan Art: an Example of a Bucchero Olpe with a Motif of Antropophagoi and the Legend of the Argonauts - Dworniak, Justyna (Acta Archaeologica Lodziensia, 2019)
The Formation of the cultures was a long and dynamic process, during which developed civilizations significantly influenced those less developed, leading to their development. However, it can be shown that in the face of the meeting, both cultures were enriched, and some elements were exchanged, which led to mutual benefits. On the Apennine Peninsula Greek culture has had a significant impact on the population living in the central of Italy. This interaction between Hellenes and the Etruscans was particularly evident in the Tyrrhenian art, which abounded in mythological representations. The article is devoted to the Etruscan ceramics bucchero with figural scenes, which is an exemplary combination of Tyrrenian native creation and the adaptation of the Greek myth. In the upper part of the olpe, the artist placed the motif of antropophagoi (cannibals), widely regarded as a typically Etruscan product. In the lower frieze, there are the heroes of the Argonaut legend - one of the oldest in Greek mythology. The first part of the article deals with the characteristics of the bucchero pottery, its origin and the method of kneading. The second one discusses olpe bucchero.